Pergerakan Character Pada Animasi Asal Usul Gapura Bajang Ratu Menggunakan Teknologi Machinima - Exwada Ardy Widyanto; Anang Kukuh Adisusilo (Melek IT : Information Technology Journal, 2017)
Majapahit kingdom was once one of the kingdoms that is very glorious in his time, many relics of kingdom Majapahit, one named Gapura Bajang Ratu. Documentation ever made using only the media book, but interest in reading in today's rarely demand. So need to do the documentation again by using the latest technology today. Technology that fits the concept of using animation. There are many kinds of animation techniques such as frame by frame and machinima animation. But there is a lack of animation with one of them in terms of time and cost. With the help of certain software for the making of characters and to record each scene in the demonstration. Character movements made include running, squatting, walking, and kneeling. Utilizing the existing software and guided by the literature that has been collected, it is appropriate to make a documentation about the Origin of Gapura Bajang Ratu.